A review on phytochemistry and pharmacology of an unexplored ethnomedicinal plant: Meyna spinosa Roxb. Ex. (2022) - Singh, Aheibam Denish; Sharma, Ajay; Mutreja, Vishal; Sohal, Harvinder Singh; Bhardwaj, Garima
Graphical abstract: Highlights: Meyna spinose is an ethnomedicinal plant mainly found in north-east part of India. Traditionally, it is used for the cure of cold, dysentery, indigestion, skin infection, intestinal worm, etc. M. spinose is well-known for its abortifacient potential. M. spinose also known to show wide range of pharmacological activities. M. spinose is a rich source of triterpenes, flavonoids, glycosides, saponins, phytosterols etc. Abstract: The significance of medicinal plants to modern allotropic healthcare is increasingly recognized in every part of the world. A global resurgence in the exploration and identification of plants of restorative significance is the outcome. Since ancient times, people are using the variety of ethnomedicinal plants for their primary health care and Meyna spinose Roxb. Ex . is one of them. It belongs to the genus Meyna and the family Rubiaceae. The plant is spread over a vast area of tropic and sub-tropical zones of the world. It is mainly found in north-east and southern part of India. It is used by the local people in various ethnomedicinal practices ranging from a simple cure for the common cold to diabetic conditions, skin infection, painful urination, hepatic disorder, intestinal worm, dysentery, indigestion, and abortifacient activity. Apart from variety of ethnomedicinal uses, it is also known for its wide range of pharmacological uses such as antimicrobial, antioxidant, cytotoxic, antidiabetic, nephroprotective and hepatoprotective potential. M. spinose also act as a stockroom for innumerable bioactive secondary metabolites (such as triterpenes, phytosterols, flavonoids, fatty alcohol, hydroxy acid etc.) and minerals (like Fe, Cu, Zn, Mo, Mn Cr. Etc.). The aim of present article is to summarize the key findings regarding the folk medicinal uses, phytochemical composition and pharmacological potential of different parts of M. spinosa along with their future prospective.